Peningkatan Hasil Belajar Tematik Terpadu Peserta Didik Menggunakan Pendekatan Konstruktivisme di Kelas V SD Negeri 58 Lubuk Buaya, Kota Padang - Zulfani, Ishma; Hamimah, Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2025)
The purpose of this study is to describe the improvement in student learning outcomes with the Constructivism approach to integrated thematic learning in class The purpose of this study is to describe the improvement in student learning outcomes with the Constructivism approach to integrated thematic learning in class V.  This type of research is PTK with a qualitative and quantitative approach. This research procedure was preceded by planning, implementation, observation and reflection. Data collection takes the form of observations and tests. This research was carried out in the second semester of the 2022/2023 academic year in two cycles. The learning outcomes of students in the attitude assessment in Cycle I were 2 people with a positive attitude and 3 people with a negative attitude. In Cycle II, there were 4 people with a positive attitude and 1 person with a negative attitude. For learning outcomes, students' knowledge and skills in cycle I obtained an average of 69.62 (K), increasing in cycle II to 84.93 (B). In the observation results, the average RPP was 84.73% (B), increasing in cycle II to 97.22% (AB). Implementation of cycle I in teacher activities averaged 84.08% (B), increasing in cycle II to 96.42% (AB). Implementation of cycle I on student activities averaged 80.35% (B), increasing in cycle II to 92.85% (AB).